Picture Composition. - WARD, PETER (Elsevier, 2002)
Behind each shot there lies an idea or purpose. When setting up a shot, the camera operator can employ a range of visual techniques that will clearly communicate the idea to an audience. Composition is the bedrock of the operator's craft, yet is seldom taught in training courses in the belief that it is an intuitive, personal skill. Peter Ward shows how composition can be learned, to enhance the quality of your work. Based on the author's own practical experience, the book deals with the methods available for resolving practical production questions such as: Does the shot composition accurately.